Free Radical Polymerization of o‐Carborane Functionalized Styrene: Effect of Substitution Position at Carbon and Boron. Issue 18 (12th May 2021) - Wen, Xin‐Yu; Cao, Ke; Wu, Ji; Zhang, Cai‐Yan; Li, Xia; Jiang, Linhai; Yang, Junxiao
Abstract: The AIBN initiated radical polymerization of o ‐carborane functionalized styrenes has been developed. The styrene decorated on the cage boron or cage carbon vertex of o ‐carboranes were all compatible with this polymerization. The Mw of the desired P[4‐(B3‐ o ‐carborane)‐styrene] and P[C1‐methylene‐ o ‐carborane‐4‐vinylbenzene] could up to 3.5×10 5 and 1.7×10 5, respectively. This work offers an efficient method for synthesis of o ‐carborane functionalized polystyrenes, which has important reference for synthesis of o ‐carborane containing polymers. Abstract : A free radical polymerization of o ‐carborane functionalized styrenes initiated by AIBN with high molecular weight was developed. The Mw of the desired P[4‐(B3‐ o ‐carborane)‐styrene] and P[C1‐methylene‐ o ‐carborane‐4‐vinylbenzene] could up to 3.5×10 5 and 1.7×10 5, respectively. This work offers an important reference for design, synthesis and application of o ‐carborane containing polymers.